Cross-partner Effects of Relationship-specific and General Internal Working Models (IWMs) and Relationship - Lowyck, Benedicto (2007)
This study examines the effects of general Internal Working Models (IWMs) related to Self-Criticism and Dependency,and relationship specific IWMs related to romantic attachment, of 45 community adults on relationshipsatisfaction as reported by their partners one year later. Results showed that Dependency was positively associated with partner relationship satisfaction, while Self-Criticism tended to be negatively related to partner relationship satisfaction. Hierarchical Multiple Regression Analysis (HMRA) showed that secure romantic attachment was positively, and dismissive romantic attachment negatively associated with partner relationship satisfaction, even when controlling for Self-criticism and Dependency.